Inactivation effect and kinetics of cathepsin L from white shrimp (Litopenaeus vannamei) by dense phase carbon dioxide - Ouyang Zheng; Xiaojie Cao; Yanqing Teng; Qinxiu Sun; Shucheng Liu (Current Research in Food Science)
The effects of dense phase carbon dioxide (DPCD) pressure and temperature on the activity of cathepsin L in white shrimp (Litopenaeus vannamei) were studied. Meanwhile the effects of DPCD and heat treatment on the activity of cathepsin L were compared. The results of inactivation kinetics showed that under the same treatment temperature, the inactivation effect of DPCD on cathepsin L increased gradually with the increase of pressure and time. The effect of DPCD pressure on the activity of cathepsin L accorded with the first-order kinetic model. Under the same treatment pressure, with the increase of temperature, the inactivation effect of cathepsin L was significant at the initial stage of DPCD treatment (rapid inactivation period), and decreased with the extension of time (stable inactivation period). The effect of DPCD treatment temperature on cathepsin L activity accorded with the first-order kinetic model at 35 °C, and two-stage kinetic model at 40–60 °C. The difference of relative enzyme activity between the two treatments showed that the dependence of DPCD on temperature was greater than that of heat. Ea, F and Ea, S of DPCD were higher than that of heat, which indicated that cathepsin L was more easily inactivated under DPCD treatment.